ENRIQUECIMENTO AMBIENTAL OLFATIVO E SONORO PARA CÃES DURANTE ADESTRAMENTO - BRUNO HENRIQUE DE SOUZA LIMONI (2025)
Promoting animal welfare is essential for both physical and emotional health, especially in potentially stressful situations such as training. Environmental enrichment is an effective strategy to reduce stress and promote behavioral and physiological balance in dogs. This study aimed to evaluate the effects of lavender essential oil, New Age music, and their combination on the welfare of dogs during training. Four treatments were tested: control (C), music (MUS), essential oil (OL), and music combined with oil (MOL). Eight dogs participated in the study. The animals were evaluated at three time points: before, during, and after training, considering the following parameters: heart rate (HR), heart rate variability (HRV), respiratory rate (RR), average ocular temperature (AOT), surface body temperature (SBT), nose temperature (NT), and tympanic temperature (TT). Behavioral assessments included the frequency of alert behaviors and signs of tension. During training, the "sit" command was applied using only the trainer’s verbal cues and hand gestures, and the "stay" command required the dogs to remain seated after the trainer moved away. The commands were applied in five-minute sessions using verbal and gestural signals. Data were analyzed using restricted maximum likelihood under a 4x4 Latin Square design, replicated over time (n = 2), with repeated measures. A mixed model was used, considering the random effects of Latin Square, animal, and period nested within the square, along with the fixed effects of treatment, time, and their interaction. Covariance structures were chosen based on the lowest AIC, and mean comparisons were performed using the Tukey-Kramer adjusted test (SAS 9.4)